Comparison and optimization of conventional and ultrasound-assisted solvent extraction for synthetization of lemongrass (Cymbopogon)-infused cooking oil - Lim, Soh Fong; Adirah, Hamdan; David Chua, Sing Ngie; Lim, Bee Huah (Wiley Periodicals LLC, 2021)
The lemongrass plant, which is widely cultivated in Asia, Australia, and Africa, has been reported to have many significant health benefits such as antimicrobial, insecticide, anticancer, fight fever, and disinfection. Therefore, it is an added benefit to have lemongrass compounds in cooking oil. This study was aimed to compare the conventional (CSE), and ultrasound-assisted solvent extraction (UASE) for citral compounds from lemongrass (Cymbopogon) leaves and to optimize the best extraction method using the response surface methodology (RSM) and ANOVA. RSM design of experiments using three types of cooking oils; palm oil, sunflower oil, and corn oil. The effect of three independent variables, which are temperature (48.2–81.8°C), extraction time (4.8–55.2 min), and solvent to leaves ratio (5.3–18.7), was investigated. The characterization of lemongrass-infused cooking oil was evaluated by Fourier transform infrared spectroscopy (FT-IR), Gas Chromatography-Mass Spectrometry (GC-MS) and Scanning Electron Microscopy (SEM) analysis for confirmation of the citral compound extraction. This extraction process is optimized using Response Surface Methodology (RSM) for producing the lemongrass-infused cooking oil. After optimization, the UASE process gives 1.009 × 106 maximum citral area for palm oil and 1.767 × 106 maximum citral area for sunflower oil. CSE process only can give 2.025 × 105 and 2.179 × 105 citral area in the GC-MS spectrum for palm oil and sunflower oil respectively. For both the UASE and the CSE, the optimum operating conditions are 81.8°C of extraction temperature and 55.2 min of extraction time except for lemongrass-infused palm oil in the CSE process with 45 min extraction time. The optimum solvent to leaves ratio varies from 5.3:1 to 12.9:1. This study found that corn oil cannot be used as a solvent to extract lemongrass-infused cooking oil due to the insignificant changes and no citral peak. The lemongrass (Cymbopogon)-infused palm oil and sunflower oil extracted using the UASE have a higher maximum citral area than the CSE process.